Developing a game and learning-centred flexible teaching model for transforming play. (3rd September 2019) - Slade, Dennis G.; Martin, Andrew J.; Watson, Geoff
ABSTRACT: Background: Slade ["Do the Structures Used by International Hockey Coaches for Practising Field-Goal Shooting Reflect Game Centred Learning Within a Representative Learning Design?" The International Journal of Sport Science and Coaching 10 (4): 655–668] argued that because no two students learn or conceive knowledge in exactly the same way, teaching contexts require a flexible approach to instruction, based on a methodological continuum of empirical to radical constructivism. In short, providing novice learners with sufficient opportunities to learn requires flexibility and a holistic experiential approach to teaching that is appropriate for the learner, activity and context. Purpose: This paper examines an evolving understanding of TGfU and Game-Centred Learning (GCL). The medium for articulating this is through the presentation of a proposed model of GCL. At the heart of this model is the notion of play, invented games and its attendant qualities of creativity, fun, affiliation and exploration. The process of arriving at this model of GCL has involved an evaluation of various models of GCL, and exploring associated questions related to teaching games, especially for the generalist teacher. Discussion: This proposed model also reflects a discussion of arguments along ideological continuums of instruction in games; for example, should fundamental movement skills (FMS) be taught before game instruction or should game pedagogy be solely based on GCL? In this paper, these positions are brought together through reference to Fundamental Game Skills [Smith, W. "Fundamental Movement Skills and Fundamental Games Skills Are Complementary Pairs and Should be Taught in Complementary Ways at all Stages of Skill Development." Sport, Education and Society 21 (3): 431–442], the application of complexity theory [Ovens, A., T. Hopper, and J. Butler. 2013. Complexity Thinking in Physical Education: Reframing Curriculum, Pedagogy and Research . Oxon: Routledge], and complementary learning in skill acquisition [Kelso, J. A. S., and D. A. Engstrom. 2006. The Complementary Nature . Cambridge, MA: MIT Press]. Smith's practitioner position provides further justification for a GCL model from a skill acquisition perspective. Conclusion: The proposed model of GCL focuses on flexibility and pragmatism, with the intent of making a GCL approach accessible to those who teach games to novices or to more experienced athletes.